Grave Pilgrimage Tradition of Pekalongan Community as Self Healing in a Psychological Perspective - Zulfa, Nadhifatuz; Himawanti, Izza; Fateha, Siti (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Human life must have many problems. If the problem cannot be resolved properly, it can trigger the onset of both physical and psychological illness. Grave pilgrimage is a common tradition in Indonesia. Even Rasulullah SAW himself encouraged his people to visit the graves because there is goodness there. For some people from Kota and Pekalongan Regency, visiting graves can be a means of self-healing. Based on a questionnaire analyzing the needs of visiting graves, it was found that by visiting graves, pilgrims can get peace of mind, avoid anxiety and anxiety, reduce stress, be happy in life, and problems can be resolved. In this study, the authors wanted to examine what types of healing are contained in the grave pilgrimage tradition of the Pekalongan people, so that this deeply rooted grave pilgrimage tradition can be an alternative self-healing in overcoming various kinds of problems experienced by the community. The research method used is qualitative research with a phenomenological approach. Data collection techniques using observation, interviews and limited surveys, as well as documentation. Data analysis techniques using descriptive techniques. The results of this study include the tradition of visiting graves as self-healing for the people of Pekalongan from a psychological perspective consisting of activities similar to the self-healing method, namely forgiveness, gratitude, self-compassion, mindfulness, and relaxation. In addition to containing self-healing methods, various practices carried out in the tradition of visiting the graves of the Pekalongan people contain values of worship, hospitality, and morals.